World Literature, Cosmopolitanism, Globality Beyond, Against, Post, Otherwise - Müller, Gesine; Siskind, Mariano (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2019)
In view of the current crisis of globalization, this book aims to interrogate one of its key concepts in the past decades: World Literature. In a historical moment where the established focus on transnational identities, linguistic intersections, and other cosmopolitan cultural configurations is being challenged, the contributions of this volume explore possible adjustments, critiques, reconceptualizations, or refutations of World Literature.